The early Bronze Age feature from Wilczyce, site 10, Sandomierz district – An interpretation of its functioning in light of multidimensional analysis - Jarosz, Paweł; Boroń, Tomasz; Witkowska, Barbara; Winiarska-Kabacińska, Małgorzata; Różańska-Tuta, Zuzanna; Skrzyński, Grzegorz; Osypińska, Marta; Kerneder-Gubała, Katarzyna; Szczepanek, Anita; Sołodko, Anna; Włodarczak, Piotr (the Authors, 2020)
The aim of this paper is to present the multidimensional characteristics of the feature number 4 at the site in Wilczyce located on the Sandomierz Upland. During exploration of the pit rich flint material, fragments of pottery vessels and animal bones were found and just above the bottom a “deposit” involved a human skull of the young female, two cattle mandibles, a sheep/goat tibia and astragalus, a damaged cattle scapula and radius, and a polishing stone were deposited. The C14 date obtained from the tooth from the cattle jaw was 3790 ± 35 BP. Based on the shape and the size of discovered feature it is possible to classify it as a typical storage pit but presence of “deposit” enable to postulate a ritual character of assemblage that reflect some kind of burial practices of the Mierzanowice culture. Rituals in the form of interring the dead or parts of their bodies can be found also in the Unietice culture so such features may indicate the emergence of a certain supra- -regional and cross-cultural trend in the early Bronze Age.
Keywords: Mierzanowice culture; Sandomierz Upland; funeral rite; settlement feature